2021
DOI: 10.21831/jep.v18i1.38580
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepribadian Proaktif, Communication Skills, Family Responsibilities Terhadap Kesuksesan Karir

Abstract: Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh kepribadian proaktif, keterampilan komunikasi, tanggung jawab keluarga terhadap keberhasilan karir. Sampel penelitian 158 lulusan pendidikan akuntansi. Teknik pengumpulan data menggunakan kuesioner. Data yang sudah terkumpul kemudian dianalisis menggunakan regresi berganda. Hasil penelitian menunjukkan bahwa kepribadian proaktif, keterampilan komunikasi, dan tanggung jawab keluarga berpengaruh signifikan terhadap keberhasilan karir. Individu yang memi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Conversely, if there is a decrease in the implementation of the three proactive personality indicators, it will cause a significant decrease in job performance. The results of this study consistently support and complement previous research conducted by (Susilowati et al, 2021).…”
Section: Regression Equationssupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, if there is a decrease in the implementation of the three proactive personality indicators, it will cause a significant decrease in job performance. The results of this study consistently support and complement previous research conducted by (Susilowati et al, 2021).…”
Section: Regression Equationssupporting
confidence: 91%
“…In theoretical views, studies have identified that personality has a positive impact on job satisfaction in a sustainable manner, and this occurs through three key characteristics, namely the ability to take initiative independently, orientation towards change, and focus on future aspects. In the study (Susilowati et al, 2021) There is an influence of proactive personality on job performance. The results of the above research indicate that proactive personality affects job performance.…”
Section: The Relationship Between Proactive Personality and Job Perfo...mentioning
confidence: 99%
“…Sebab, kecakapan berkomunikasi lisan sangat berpengaruh dalam memperluas pertemanan dan mitra atau relasi dalam berkarier. Komunikasi yang baik dalam aktivitas keseharian merupakan modal dan kunci sukses dalam pergaulan, terutama berkaitan dengan jenjang karier, sebab berpengaruh besar dalam membangun hubungan baik dengan pihak lain (Susilowati et al, 2021). Kepada para siswa dijelaskan pula bahwa berkomunikasi lisan yang tidak menarik, bahkan tidak baik merupakan hal yang merugikan dalam membangun dan memperluas relasi.…”
Section: Hasil Penemuan Dan Diskusiunclassified